Análise da dinâmica da renda per capita nos municípios paraibanos, no período de 1970 a 2008 - Tavares, Marcella Braga (2011)
The overall objective of this dissertation is to investigate the behavior of GDP per capita in Paraíba municipalities, as well as the existence of an income convergence behavior in the time period between the years 1970 to 1996 and from 1999 to 2008. To that end, we performed exploratory analysis of spatial data to describe and visualize spatial distributions by analyzing the spatial statistics of the Moran's I and LISA. In order to empirically test the convergence of income, we used various econometric techniques, namely: Method of Ordinary Least Squares (OLS), OLS with spatial correction, quantile regressions and Markov chain. The variables used in this work are from different sources, which are calculated from the database available on the website of IPEADATA. The results of the analysis of Moran's I and LISA for the rate of growth of GDP per capita suggest the existence of a process of income convergence between the municipalities of Paraíba in the study period. The OLS method proved not to be the most appropriate technique to analyze income convergence. On the other hand, there was the results of models of spatial econometrics, SEM, and SAR, strong evidence of a process of spatial convergence of income per capita among municipalities Paraíba. The convergence behavior was also observed in the quantile regression model, since the coefficient of initial per capita GDP variable appeared negative in the whole distribution. Finally, the Markov chain analysis showed that a number of municipalities that are inserted in the Zona da Mata focus on the platform defined as the richest municipalities in the initial period that remain rich in the final period analyzed.